Preparation method of copper-doped silicon carbide composite wave absorbing material
By mixing copper nitrate hexafluorosilicate hexafluorosilicate in methanol solution and adding pyrazine as ligand, fluorosilicate porous material was prepared, coated with dopamine hydrochloride, and finally carbonized at high temperature, the current solution was solved There is a problem of poor absorption capacity of composite wave absorbing materials, which has achieved efficient preparation of copper-doped silicon carbide composite materials and excellent electromagnetic wave absorption performance.
Patent Information
- Application Number
- CN202211587781.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-12-05
AI Technical Summary
The existing composite wave absorbing materials have poor wave absorption capabilities, which are difficult to meet the needs of strong electromagnetic wave absorption performance, wide frequency band, thin thickness and light weight.
By mixing copper nitrate hexafluorosilicate hexafluorosilicate in methanol solution and adding pyrazine as ligand, fluorosilicate porous material is obtained by in situ synthesis, followed by dopamine hydrochloride, and finally carbonization is carried out at high temperature , a copper-doped silicon carbide composite absorbing material was prepared.
The efficient preparation of copper-doped silicon carbide composite materials is achieved, and the material exhibits extremely strong reflection loss and wide effective absorption bandwidth, which is suitable for electromagnetic wave absorption applications.
Smart Images

Figure CN116161664B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic wave absorbing materials, and in particular relates to a method for preparing a copper-doped silicon carbide composite absorbing material. Background Art
[0002] As the electromagnetic environment becomes increasingly complex, it is extremely important to explore electromagnetic wave absorbing materials with wide absorption bandwidth, thin thickness, light weight and strong wave absorption performance. Electromagnetic wave absorbing materials are mainly divided into three types according to the wave absorption mechanism of the materials: dielectric loss type (materials such as graphite and conductive polymers), magnetic loss type (magnetic materials such as ferrite and hydroxy iron) and other loss types (nanomaterials and metamaterials, etc.). These materials have great application prospects in the fields of medicine, industry and modern military.
[0003] Metal-organic frameworks (MOFs) are hybrids composed of metal ions and organic ligands with periodic coordination. The derived absorbers have attracted much attention due to their porosity, adjustable nanostructure and easy-to-control electromagnetic wave absorption mechanism. For example, Professor Wu Hongjing of Northwestern Polytechnical University successfully synthesized and optimized composite copper-doped sulfide carbon materials using Cu / S-MOF, which showed excellent performance in the absorption range (bandwidth of 6.80GHz); in addition, the new fluorosilicate porous hybrid material (SiFSIX) is an isoporous nanoporous MOF with octahedral coordination and highly adjustable ligands. Using this SiFSIX material as a precursor, a variety of composite absorbers can be derived through different post-treatments, which can not only improve the conductivity but also improve the absorption performance. For example, Chen Jingpeng from the University of Chinese Academy of Sciences prepared SiC whisker / reduced graphene oxide aerogel using in-situ growth and physical mixing methods. The addition of Si base can improve the interface impedance between free space and absorber, thereby obtaining excellent microwave absorption performance (reflection loss is -60.05dB at 17.12GHz with a thickness of 2.00mm). Therefore, the preparation of copper-doped fluorosilicic acid composite absorber by combining copper and silicon is a new type of electromagnetic wave absorbing material. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a copper-doped silicon carbide composite wave-absorbing material, thereby solving the problem that the existing composite wave-absorbing material has poor wave-absorbing ability.
[0005] The technical solution adopted by the present invention is a method for preparing a copper-doped silicon carbide composite absorbing material, and the specific operating steps are as follows:
[0006] The preparation method of copper-doped silicon carbide composite absorbing material has the following specific steps:
[0007] Step 1, dissolving copper nitrate hexahydrate and ammonium hexafluorosilicate in a methanol solution to obtain a solution A; dissolving pyrazine in a methanol solution to obtain a pyrazine ligand solution B;
[0008] Step 2, heating solution A under reflux and stirring at a certain temperature;
[0009] Step 3, adding pyrazine ligand solution B to solution A and mixing, and continuing to reflux and stir at a certain temperature to obtain a mixed solution;
[0010] Step 4, centrifuging the mixed solution in step 3 to collect the powder, washing it, and finally drying it in a vacuum drying oven to obtain a novel fluorosilicate porous material powder C;
[0011] Step 5, dissolving the novel fluorosilicate porous material powder C in methanol to form a solution D;
[0012] Step 6, dissolving dopamine hydrochloride (PDA) in methanol to form solution E;
[0013] Step 7, solution D is mixed with solution E, stirred at room temperature, washed, and finally dried in a vacuum oven to obtain a fluorosilicate porous material coated with dopamine hydrochloride.
[0014] Step 8: In a nitrogen environment, the dopamine hydrochloride-coated fluorosilicate porous material is placed in a porcelain boat, placed in a tube furnace, and annealed to obtain a copper-doped silicon carbide composite carbon material.
[0015] The present invention is also characterized in that:
[0016] In step 1, the Cu(NO3)2·6H2O can be replaced by copper salts such as copper sulfate, copper acetate, and copper chloride, and the (NH4)2SiF6 can be replaced by fluorosilicate.
[0017] The molar ratio of Cu(NO3)2·6H2O to (NH4)2SiF6 in step 1 is 1:1.
[0018] In step 2, the heating temperature is 60° C. to 80° C., and the reflux time is 2 h to 4 h.
[0019] The molar ratio of pyrazine to Cu(NO3)2·6H2O and (NH4)2SiF6 is 2:1:1, and the volume ratio of methanol in solution A and pyrazine ligand solution B is 1:1.
[0020] The heating temperature in step 3 is 60° C. to 80° C., and the reflux time is 1 h to 4 h.
[0021] In step 4, water or ethanol can be used for washing, the drying temperature is 60° C. to 100° C., and the drying time is 12 h to 24 h.
[0022] The volume ratio of ethanol in step 5 and step 6 is 1:1.
[0023] In step 6, the mass ratio of dopamine hydrochloride PDA to the SiFSIX-3-Cu powder C is 1:1.
[0024] In step 7, washing is performed with water or ethanol, the drying temperature is 60 to 100° C., and the drying time is 12 to 24 hours. The synthesis principle of the key steps in the present invention is:
[0025] Using pyrazine as a ligand, copper nitrate hexahydrate and ammonium hexafluorosilicate were mixed as ligands to synthesize a new type of fluorosilicate porous material (SiFSIX-3-Cu) in situ. A layer of dopamine hydrochloride (PDA) was coated on the outer layer of the material, which can be used as a buffer layer to protect the copper-doped fluorosilicate porous material from damage during subsequent operations. Finally, after high-temperature heat treatment for carbonization, the conductivity of the material was increased to obtain a copper-doped silicon carbide composite absorber (SiFSIX-3-Cu@C).
[0026] The beneficial effects of the present invention are:
[0027] (1) SiFSIX-3-Cu is coated with a layer of dopamine hydrochloride (PDA) and converted into a copper-doped silicon carbide composite material during the subsequent heat treatment process. The fluorosilicate porous material can be easily regulated by changing the length of the ligand (pyrazine) and the functional group (copper ion) to adjust the microwave absorption performance.
[0028] (2) The present invention provides a synthesis strategy for copper-doped silicon carbide composite carbon materials. The material was used to test the wave absorption performance, which showed extremely strong reflection loss and a wide effective absorption bandwidth (<-10dB).
[0029] (3) The preparation method of the present invention is simple, efficient, and easy to implement, and is a synthetic method that can be adopted on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a flow chart of the method for preparing the copper-doped silicon carbide composite absorbing material of the present invention;
[0031] Figure 2 is the XRD diagram of the fluorosilicate porous material coated with dopamine hydrochloride of the present invention;
[0032] Figure 3 This is the XRD diagram of the copper-doped silicon carbide composite absorbing material of the present invention;
[0033] Figure 4 is a graph of reflection loss values of the copper-doped silicon carbide composite absorbing material of the present invention;
[0034] Figure 5is a diagram of the wave absorption bandwidth of the copper-doped silicon carbide composite wave absorbing material of the present invention;
[0035] Figure 6 is a graph of the real part value ε' of the dielectric loss of the copper-doped silicon carbide composite absorbing material of the present invention;
[0036] Figure 7 is a graph of the imaginary value ε" of the dielectric loss of the copper-doped silicon carbide composite absorbing material of the present invention;
[0037] Figure 8 is the tangent value of the dielectric loss of the copper-doped silicon carbide composite absorbing material of the present invention, Tanδ ε picture;
[0038] Fig. 9 is a graph of the real value μ' of the magnetic loss of the copper-doped silicon carbide composite absorbing material of the present invention;
[0039] Fig.10 is a graph of the imaginary value μ" of the magnetic loss of the copper-doped silicon carbide composite absorbing material of the present invention;
[0040] Fig.11 is the tangent value of the magnetic loss of the copper-doped silicon carbide composite absorbing material of the present invention, Tanδ μ picture. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments.
[0042] Embodiment 1:
[0043] The preparation method of the copper-doped silicon carbide composite absorbing material of the present invention is as follows: Figure 1 The specific steps are as follows:
[0044] Step 1, dissolve copper nitrate hexahydrate (1 mmol, 0.2416 g) and ammonium hexafluorosilicate (1 mmol, 0.1782 g) in a methanol solution (15 ml) to obtain solution A; dissolve pyrazine (2 mmol, 0.16018 g) in a methanol solution (15 ml) to obtain solution B;
[0045] Step 2, heating solution A at 60° C. with stirring and reflux for 2 hours;
[0046] Step 3, adding solution B to solution A and mixing, and continuing to heat, stir and reflux at 60° C. for 8 hours;
[0047] Step 4, collecting the powder by centrifugation, washing it with methanol, and finally placing it in a vacuum drying oven for 12 hours to obtain a purple fluorosilicate porous material powder C;
[0048] Step 5, taking 0.5 g of fluorosilicate porous material powder C and dissolving it in 25 ml of methanol to form a solution D;
[0049] Step 6, 0.3 g of dopamine hydrochloride PDA was dissolved in 25 ml of methanol to form solution E;
[0050] Step 7, solution D is mixed with solution E, stirred at room temperature for 24 hours, washed with methanol, and finally dried in a vacuum oven at 60° C. to obtain a fluorosilicate porous material coated with dopamine hydrochloride;
[0051] Step 8: In a nitrogen environment, the fluorosilicate porous material coated with dopamine hydrochloride is placed in a porcelain boat, placed in a tube furnace, and annealed at 900° C. for 2 hours to obtain a copper-doped silicon carbide composite carbon material.
[0052] Embodiment 2:
[0053] Step 1, copper sulfate (1 mmol) and ammonium hexafluorosilicate (1 mmol, 0.1782 g) were dissolved in a methanol solution (15 ml) to obtain a solution A; pyrazine (2 mmol, 0.16018 g) was dissolved in a methanol solution (15 ml) to obtain a solution B;
[0054] Step 2, heating solution A at 60° C. with stirring and reflux for 2 hours;
[0055] Step 3, adding solution B to solution A and mixing, and continuing to heat, stir and reflux at 80° C. for 4 hours;
[0056] Step 4, collecting the powder by centrifugation, washing it with methanol, and finally placing it in a vacuum drying oven for 12 hours to obtain a purple fluorosilicate porous material powder C;
[0057] Step 5, taking 0.5 g of fluorosilicate porous material powder C and dissolving it in 25 ml of methanol to form a solution D;
[0058] Step 6, 0.3 g of dopamine hydrochloride was dissolved in 25 ml of methanol to form solution E;
[0059] Step 7, solution D is mixed with solution E, stirred at room temperature for 24 hours, washed with methanol, and finally dried in a vacuum oven at 60° C. to obtain a fluorosilicate porous material coated with dopamine hydrochloride;
[0060] Step 8: In a nitrogen environment, the fluorosilicate porous material coated with dopamine hydrochloride is placed in a porcelain boat, placed in a tube furnace, and annealed at 900° C. for 2 hours to obtain a copper-doped silicon carbide composite carbon material.
[0061] Embodiment 3:
[0062] Step 1, dissolving copper nitrate hexahydrate (1 mmol) and sodium hexafluorosilicate (1 mmol) in a methanol solution (15 ml) to obtain solution A; dissolving pyrazine (2 mmol, 0.16018 g) in an ethanol solution (15 ml) to obtain solution B;
[0063] Step 2, heating solution A at 60° C. with stirring and reflux for 2 hours;
[0064] Step 3, adding solution B to solution A and mixing, and continuing to heat, stir and reflux at 60° C. for 4 hours;
[0065] Step 4, collecting the powder by centrifugation, washing it with methanol, and finally placing it in a vacuum drying oven for 12 hours to obtain a purple fluorosilicate porous material powder C;
[0066] Step 5, taking 0.5 g of fluorosilicate porous material powder C and dissolving it in 25 ml of methanol to form a solution D;
[0067] Step 6, 0.3 g of dopamine hydrochloride was dissolved in 25 ml of methanol to form solution E;
[0068] Step 7, solution D is mixed with solution E, stirred at room temperature for 24 hours, washed with methanol, and finally dried in a vacuum oven at 60° C. to obtain a fluorosilicate porous material coated with dopamine hydrochloride;
[0069] Step 8: In a nitrogen environment, the fluorosilicate porous material coated with dopamine hydrochloride is placed in a porcelain boat, placed in a tube furnace, and annealed at 1000° C. for 2 hours to obtain a copper-doped silicon carbide composite carbon material.
[0070] Embodiment 4:
[0071] Step 1, dissolving copper sulfate (1 mmol, 0.2416 g) and ammonium hexafluorosilicate (1 mmol, 0.1782 g) in a methanol solution (15 ml) to obtain a solution A; Step 3, dissolving pyrazine (2 mmol, 0.16018 g) in a methanol solution (15 ml) to obtain a solution B;
[0072] Step 2, heating solution A at 60° C. with stirring and reflux for 2 hours;
[0073] Step 3, adding solution B to solution A and mixing, and continuing to heat, stir and reflux at 60° C. for 8 hours;
[0074] Step 4, collecting the powder by centrifugation, washing it with methanol, and finally placing it in a vacuum drying oven for 12 hours to obtain a purple fluorosilicate porous material powder C;
[0075] Step 5, taking 0.5 g of fluorosilicate porous material powder C and dissolving it in 25 ml of methanol to form a solution D;
[0076] Step 6, 0.3 g of dopamine hydrochloride was dissolved in 25 ml of methanol to form solution E;
[0077] Step 7, solution D is mixed with solution E, stirred at room temperature for 24 hours, washed with methanol, and finally dried in a vacuum oven at 60° C. to obtain a fluorosilicate porous material coated with dopamine hydrochloride;
[0078] Step 8: In a nitrogen environment, the fluorosilicate porous material coated with dopamine hydrochloride is placed in a porcelain boat, placed in a tube furnace, and annealed at 800° C. for 3 hours to obtain a copper-doped silicon carbide composite carbon material SiFSIX-3-Cu@C.
[0079] Embodiment 5:
[0080] Step 1, dissolve copper nitrate hexahydrate (Cu(NO3)2·6H2O) (1 mmol, 0.2416 g) and ammonium hexafluorosilicate ((NH4)2SiF6) (1 mmol, 0.1782 g) in a methanol solution (15 ml) to obtain solution A; dissolve pyrazine (2 mmol, 0.16018 g) in a methanol solution (15 ml) to obtain solution B;
[0081] Step 2, heating solution A at 60° C. with stirring and reflux for 2 hours;
[0082] Step 3, adding solution B to solution A and mixing, and continuing to heat, stir and reflux at 60° C. for 4 hours;
[0083] Step 4, collecting the powder by centrifugation, washing it with methanol, and finally placing it in a vacuum drying oven for 12 hours to obtain a purple fluorosilicate porous material powder C;
[0084] Step 5, taking 0.5 g of fluorosilicate porous material powder C and dissolving it in 25 ml of methanol to form a solution D;
[0085] Step 6, 0.5 g of dopamine hydrochloride was dissolved in 25 ml of methanol to form solution E;
[0086] Step 7, solution D is mixed with solution E, stirred at room temperature for 24 hours, washed with methanol, and finally dried in a vacuum oven at 60° C. to obtain a fluorosilicate porous material coated with dopamine hydrochloride;
[0087] Step 8: In a nitrogen environment, the fluorosilicate porous material coated with dopamine hydrochloride is placed in a porcelain boat, placed in a tube furnace, and annealed at 900° C. for 2 hours to obtain a copper-doped silicon carbide composite carbon material.
[0088] According to the synthesis process of Examples 1 to 5 and the test results of electromagnetic wave absorption performance, in Example 1, copper nitrate hexahydrate (1mmol, 0.2416g), ammonium hexafluorosilicate (1mmol, 0.1782g), methanol (15mL), and dopamine hydrochloride (0.5g) are the most preferred options. In the electromagnetic wave absorption performance test, when the material is 2.5mm, the reflection loss value of the copper-doped silicon carbide composite material reaches -43dB. At 2.0mm, the effective absorption bandwidth is 11.52GHz to 17.92GHz, covering the entire Ku band and part of the X band. At 2.5mm, the effective absorption bandwidth is 9.12GHz to 14.75GHz, covering the entire X band and part of the Ku band. It shows that the prepared composite material has high wave absorption performance.
[0089] like Figure 2 The XRD diagrams of the fluorosilicate porous material and the fluorosilicate porous material coated with dopamine hydrochloride of the present invention are shown in Figure 1. After the material is coated with dopamine, a carbon coating peak appears, and the good crystalline structure of the precursor is maintained.
[0090] like Figure 3 The XRD diagram of the fluorosilicate porous material and the copper-doped silicon carbide composite absorbing material ( of the present invention. By comparing with the standard card, the crystal planes of Si, CuF2, SiC and C can be observed, and the stability before and after treatment is maintained.
[0091] like Figure 4 The figure is the reflection loss value (RL) of the copper-doped silicon carbide composite absorbing material of the present invention at different thicknesses. It can be seen that when the thickness is 2.5 mm, the reflection loss value of the copper-doped silicon carbide composite absorbing material reaches -43 dB, indicating that the material has good electromagnetic wave absorption performance.
[0092] like Figure 5 This is the bandwidth diagram of the copper-doped silicon carbide composite absorbing material of the present invention. At 2.0 mm, the effective absorption bandwidth is 11.52 GHz to 17.92 GHz, covering the entire Ku band and part of the X band. At 2.5 mm, the effective absorption bandwidth is 9.12 GHz to 14.75 GHz, covering the entire X band and part of the Ku band.
[0093] like Figure 6 This is a real part graph of the dielectric loss of the copper-doped silicon carbide composite absorbing material of the present invention. In the low-band 2GHz to 7GHz, the real part value of the dielectric constant (ε') gradually decreases; in the 7GHz to 18GHz, the real part value of the dielectric constant (ε') decreases in a gradient.
[0094] like Figure 7This is an imaginary part diagram of the dielectric loss of the copper-doped silicon carbide composite absorbing material of the present invention. The imaginary part value of the dielectric constant (ε") decreases within 2 GHz to 7 GHz and increases gradually within 8 GHz to 18 GHz.
[0095] like Figure 8 The tangent value of dielectric loss (Tanδ ε =ε" / ε') decreases slowly and then increases sharply in the range of 2GHz to 18GHz, but the value increases between 0.35 and 0.8.
[0096] like Fig. 9 This is a real part diagram of the magnetic loss of the copper-doped silicon carbide composite absorbing material of the present invention. The real part value (μ') of the magnetic loss increases sharply within 2 GHz to 6 GHz, and then remains basically stable within 8 GHz to 18 GHz.
[0097] like Fig.10 This is the imaginary part diagram of the magnetic loss of the copper-doped silicon carbide composite absorbing material of the present invention. The imaginary part value (μ") of the magnetic loss rises in an oscillating manner between 2 GHz and 18 GHz.
[0098] like Fig.11 The tangent value of magnetic loss (Tanδ μ =μ" / μ') rises in an oscillating manner from 2GHz to 18GHz, but its values are all less than 0.3.
[0099] Combination Figures 1 to 11 The results show that in the electromagnetic wave absorption performance test, the reflection loss value of the copper-doped silicon carbide composite material reaches -43dB at 2.5mm. At 2.0mm, the effective absorption bandwidth is 11.52GHz~17.92GHz, covering the entire Ku band and part of the X band. At 2.5mm, the effective absorption bandwidth is 9.12GHz~14.75GHz, covering the entire X band and part of the Ku band, indicating that the prepared composite material has high wave absorption performance. In addition, the magnetic permeability tangent (Tanδ μ ) is smaller than the dielectric constant tangent (Tanδ ε ), which also shows that magnetic loss plays an important role in the wave absorption process.
Claims
1. A method for preparing a copper-doped silicon carbide composite absorbing material, characterized in that: The specific steps are as follows: Step 1, dissolving copper nitrate hexahydrate and ammonium hexafluorosilicate in a methanol solution to obtain a solution A; dissolving pyrazine in a methanol solution to obtain a pyrazine ligand solution B; The molar ratio of Cu(NO3)2·6H2O to (NH4)2SiF6 in step 1 is 1:1; The molar ratio of pyrazine to Cu(NO3)2·6H2O and (NH4)2SiF6 is 2:1:1, and the volume ratio of methanol in solution A and pyrazine ligand solution B is 1:1; Step 2, heating solution A under reflux and stirring at a certain temperature; In step 2, the heating temperature is 60°C to 80°C, and the reflux time is 2h to 4h; Step 3, adding pyrazine ligand solution B to solution A and mixing, and continuing to reflux and stir at a certain temperature to obtain a mixed solution; The heating temperature in step 3 is 60°C to 80°C, and the reflux time is 1h to 4h; Step 4, centrifuging the mixed solution in step 3 to collect the powder, washing it, and finally drying it in a vacuum drying oven to obtain a novel fluorosilicate porous material powder C; Step 5, dissolving the fluorosilicate porous material powder C in methanol to form a solution D; Step 6, dissolving dopamine hydrochloride PDA in methanol to form solution E; In step 6, the mass ratio of dopamine hydrochloride PDA to the fluorosilicate porous material powder C is 1:1; Step 7, solution D is mixed with solution E, stirred at room temperature, washed, and finally dried in a vacuum oven to obtain a fluorosilicate porous material coated with dopamine hydrochloride; Step 8: In a nitrogen environment, the dopamine hydrochloride-coated fluorosilicate porous material is placed in a porcelain boat, placed in a tube furnace, and annealed to obtain a copper-doped silicon carbide composite carbon material.
2. The method for preparing the copper-doped silicon carbide composite absorbing material according to claim 1, characterized in that: The copper nitrate hexahydrate in step 1 can be replaced by copper sulfate, copper acetate, copper chloride and other copper salts, and the ammonium hexafluorosilicate can be replaced by fluorosilicate.
3. The method for preparing the copper-doped silicon carbide composite absorbing material according to claim 1, characterized in that: In step 4, water or ethanol can be used for washing, and the drying temperature is 60 o C~100 o C, drying time is 12h ~24h.
4. The method for preparing the copper-doped silicon carbide composite absorbing material according to claim 1, characterized in that: The volume ratio of methanol in step 5 and step 6 is 1:
1.
5. The method for preparing the copper-doped silicon carbide composite absorbing material according to claim 1, characterized in that: In step 7, washing is performed with water or ethanol, and the drying temperature is 60 to 100 o C, drying time is 12h~24h.